Voices, Chronotopes, and Genre: Dialogical Self Construction in I Know Why The Caged Bird Sings - Akter, Shirin (International Journal of Language and Literary Studies, 2025)
The present study examines the influences of voices and spaces in the self-construction of Maya in I Know Why the Caged Bird Sings. Drawing on Hubert Hermans’ concept of the dialogical self, which is conceptualized on Bakhtin’s theory of polyphony, the study explores Maya’s consciousness as a fluid boundary that receives, accommodates, and adjusts to the influences of others. In this construction, Angelou creates a dialogical self that is populated by the voices of other people and decentralized with highly open boundaries. Angelou weaves elements of African American blues and spirituals with Western literary traditions. By blending these diverse traditions, Angelou shapes Maya’s narrative voice as a rich interplay of linguistic, racial, and gendered positions. This narrative complexity reflects Angelou’s skilful engagement with cultural traditions and histories. Through her transcendent storytelling, Angelou defies genre boundaries and constructs Maya’s selfhood as a powerful tapestry of cultural influences. In doing so, Angelou asserts herself as a polyphonic voice, reinforcing the dynamic interplay of multiple perspectives within her work.